Stealing your life : the ultimate identity theft prevention plan - Abagnale, Frank W., 1948- (New York, NY : Broadway Books, 2007)
Charismatic former forger Abagnale exposes the tactics of today's identity theft criminals and offers powerful strategies to thwart them, based on his second career as an acclaimed fraud-fighting consultant. When Abagnale trains law enforcement officers about identity theft, he asks for their names and addresses and nothing more. In a matter of hours he can obtain everything he would need to steal their lives: Social Security numbers, dates of birth, current salaries, checking account numbers, the names of everyone in their families, and more. This illustrates how easy it is for anyone from anywhere in the world to assume our identities and in a matter of hours devastate our lives in ways that can take years to recover from. Abagnale offers dozens of concrete steps to transform anyone from an easy mark into a hard case that criminals are likely to bypass.--From publisher description.
The sweetest con of all -- The next victim, and it's you -- The road to becoming you -- It could be public enemy number 1 or it could be grandma -- What your duplicate is doing as you -- The twenty steps to prevent identity theft -- Understanding trade lines and the meaning of R2 -- Remember that privacy statement you threw away -- My farewell to checks -- They got me, now what? -- The crime that keeps on stealing -- Write your company and congressman now! -- Staying two steps ahead (or three).
Keywords: Identity theft -- United States; Identity theft -- United States -- Prevention; Identiteit; Fraude; Preventie; Verenigde Staten